Policies on language education in Indonesia - Hamied, Fuad Abdul; Musthafa, Bachrudin (Universitas Pendidikan Indonesia, 2019)
This article discusses policies on language education in Indonesia by covering six major sections. The linguistic make-up and history of languages currently spoken in the country are first introduced as the background to the discussion.Â Then, building on the background factual information on the language education policies once adopted in Indonesia, a review and critical discussion regarding the design, implementation, and evaluation of the language education policies in the country are put forward. This is then followed by an elaboration of how currently adopted language education policies position different languages and what status and roles each language is accorded, and how these statuses and roles compare with English. Afterward, a prediction for the future status and role of the relevant languages under discussion is brought to light. Finally, a conclusion is made, accompanied by suggestions for further reading which will enable enrichment of knowledge-base on relevant aspects of policies on language education in Indonesia.